2017
DOI: 10.5714/cl.2017.21.051
|View full text |Cite
|
Sign up to set email alerts
|

Effect of carbonization temperature on crystalline structure and properties of isotropic pitch-based carbon fiber

Abstract: Isotropic pitch-based fibers produced from coal tar pitch with the melt-blowing method were carbonized at temperatures ranging from 800 to 1600 o C to investigate their crystalline structure and physical properties as a function of the carbonization temperature. The in-plane crystallite size (L a ) of the carbonized pitch fiber from X-ray diffraction increased monotonously by increasing the carbonization temperature resulting in a gradual increase in the electrical conductivity from 169 to 3800 S/cm. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 20 publications
(34 reference statements)
2
13
0
Order By: Relevance
“…Peaks could be located around 1600 cm −1 and 1000 cm −1 for Cu-lignin samples, which indicated that graphene layers were detected. Both samples with lignin only and Cu-lignin mixture samples heated at 600 °C had significantly higher carbonization yields than 800 °C, followed by 1000 °C, which had the same trend as reported by Kim’s group [22]. …”
Section: Resultssupporting
confidence: 81%
“…Peaks could be located around 1600 cm −1 and 1000 cm −1 for Cu-lignin samples, which indicated that graphene layers were detected. Both samples with lignin only and Cu-lignin mixture samples heated at 600 °C had significantly higher carbonization yields than 800 °C, followed by 1000 °C, which had the same trend as reported by Kim’s group [22]. …”
Section: Resultssupporting
confidence: 81%
“…The broadness of G band also confirmed this observation, with full width at half-maximum values (ca. 89-97) comparable to those reported for stabilised pitch fibres [34]; the values for D band are higher due to a large contribution of defects. SEM (Figure 8) explored the morphology of the fibres upon stabilisation.…”
Section: Wavenumber (Cm -1 )supporting
confidence: 76%
“…The y-axis intercept is significantly lower than unity in both cases with (84.0 ± 1.2)% and (82.77 ± 0.47)%. A plausible explanation for the specific conductance reductions at zero burn-off are chemical or changes of the crystalline structure [67] at the early stages of the activation process. Considering the delay of burn-off and specific ECAS development discussed in Section 3, it seems more likely, that the formation of oxygen-containing functionalities is responsible for the apparent conductance changes at zero-burn-off.…”
Section: Electrical Conductivity Changes With Activationmentioning
confidence: 99%